Wykorzystanie ekonometrycznych modeli sprzedaży do opisu "bąbli promocyjnych" i budowy scenariuszy cenowych akcji promocyjnych - Błażejowski, Marcin (Using of Econometric Sales Models for Describing "Promotions Bubbles" Effects and Building Different Promotions Scenario, 2006)
Producers of different products relatively often and quite regular introduce sales promotions to the market by deep and periodic lower of real price of items. The most often, range of reaction of the demand in response to such interference for particular promotion campaigns is not the same in time, although the period of campaign is not the same than period of demand reaction, so effectiveness of different campaigns is limited. The aim of the paper is to show results of econometric modeling the "promotions bubbles" (effects of the promotions) based on sales daily data derived from one of the Toruń's hypermarket and use these models for building different promotions scenario according to different parameters values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 177-186